Exploring chalcolithic diet and mobility of humans and animals from Perdigões site - Zalaite, Indre (2016)
Chalcolithic diet at Perdigões (Reguengos de Monsaraz) was investigated using stable carbon and nitrogen isotope analysis of human bone collagen. Strontium isotopes of faunal dental enamel were used to establish the site local range and to distinguish the presence of non-local individuals. ATR-FTIR and EA analysis were used to determine the degree of bone diagenesis and to evaluate the reliability of the stable isotopic composition for paleodietary reconstruction. The individuals from which paleodietary results were obtained had a diet based on C3 terrestrial resources and some animal protein. Data from Perdigões site, was compared with the published data from other Iberian Chalcolithic populations. Site comparison revealed that diet through Iberian Peninsula have mainly maintained terrestrial dietary focus consistent with animal husbandry and farming on C3 plants with occasional intake of freshwater or marine resources. Strontium isotopic composition of enamel revealed that some of the individuals from Perdigões site were non-local; Resumo: A dieta de indivíduos do período Calcolítico dos Perdigões (Reguengos de Monsaraz) foi investigada através de análise de isótopos estáveis de carbono e azoto no colagénio ósseo. Isótopos de estrôncio do esmalte dentário de fauna foram utilizados para estabelecer o sinal local dos Perdigões, permitindo distinguir a presença de alguns indivíduos e fauna não-locais. A avaliação da diagénese óssea foi efectuada através de análises realizadas com analisador elementar e com ATR-FTIR, de forma a validar dos resultados isotópicos obtidos. Os indivíduos para os quais foi possivel obter resultados isotópicos de carbono e azoto apresentam uma dieta baseada em recursos terrestres, plantas C3, e alguma proteína animal. A comparação efectuada com outros sitios arqueológicos da Peninsula Ibérica revelaram que a dieta das populações é sobretudo feita à base de plantas C3, com ingestão de alguma proteina animal e ingestão ocasional de produtos marinhos ou provenientes de água doce.